Prevalence of Malaria and Associated Factors Among Children Attending Health Institutions at South Gondar Zone, Northwest Ethiopia: A Cross-Sectional Study - Lemma Workineh MSc; Misganew Lakew BSc; Shega Dires BSc; Teklehaimanot Kiros MSc; Shewaneh Damtie MSc; Wasihun Hailemichael MSc; Dassalegn Muleta MSc; Tahir Eyayu MSc (SAGE Publishing, 2021)
Malaria is a fatal disease among children in malaria-prone locations such as Addis Zemen and Woreta because of their weak immune systems. Despite the severity of the disease in children, the majority of research conducted in Ethiopia has focused on adult populations rather than children. Furthermore, there is no data on malaria prevalence, risk factors, or parasite density among children in the Addis Zemen and Woreta catchment areas. Therefore, this study was aimed at filling the above gap in the study area. About 422 children were enrolled in the study by systematic sampling technique. A capillary blood sample was collected from each child to do blood film. The overall prevalence of malaria among children attending South Gonder health institutions was 14.7%. The majority of parasite density was moderate parasitemia followed by low parasitemia, giving 71.0% and 16.0%, respectively. Malaria parasite infection was linked to a history of malaria and the presence of stagnant water near a home, but utilization of insecticide-treated bed nets was found to be protective against the infection. Therefore, health education should be strengthened on proper utilization of bed nets, indoor residual spraying, removing stagnant water by discarding old tires that may collect rainwater, and removing debris from streams so streams flow more freely.